2016
DOI: 10.1038/pr.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

Soluble receptor and gene polymorphism for AGE: relationship with obesity and cardiovascular risks

Abstract: Background: Obesity in adolescents has quadrupled in the past 30 y. Markers for cardiovascular risks are needed in this population. We hypothesized that soluble receptor for advanced glycation end products (sRAGE) and asymmetric dimethyl arginine (ADMA) can correlate with carotid intimamedia thickness (cIMT), a known index of subclinical atherosclerosis. We also aimed to evaluate the frequency of (Gly82Ser) RAGE gene polymorphism in obese adolescents. Methods: Obese and nonobese adolescents were evaluated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…even if not accompanied by additional cardiometabolic risk factors such as elevated BP, AIP, and IR, associates with low sRAGE and esRAGE levels. In contrast with our hypothesis, the missing association between sRAGE and/or esRAGE and measures of obesity in some but not all studies [13][14][15][16][17][18][19][20][21][22][39][40][41][42][43] might not be related to the metabolically healthy obese phenotype. Since in non-diabetic adults low sRAGE levels associate independently with a future risk of cardiometabolic diseases and mortality [24], we might presume that a metabolically healthy obese phenotype is far from being a benign condition [44,45].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…even if not accompanied by additional cardiometabolic risk factors such as elevated BP, AIP, and IR, associates with low sRAGE and esRAGE levels. In contrast with our hypothesis, the missing association between sRAGE and/or esRAGE and measures of obesity in some but not all studies [13][14][15][16][17][18][19][20][21][22][39][40][41][42][43] might not be related to the metabolically healthy obese phenotype. Since in non-diabetic adults low sRAGE levels associate independently with a future risk of cardiometabolic diseases and mortality [24], we might presume that a metabolically healthy obese phenotype is far from being a benign condition [44,45].…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of this allele in Slovaks is too low (about 4 %) [58] to explain the obesity-associated decline in sRAGE. However, in obese Egyptian adolescents, the prevalence of this mutated allele is much higher (23 %), and the homozygous carriers present significantly lower sRAGE levels in comparison to those carrying the dominant allele [20].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, recent studies suggest links between the Ser allele of the Gly82Ser AGER polymorphism to obesity risk and that the Ser allele was associated with higher levels of sRAGE in children [43]. A distinct study demonstrated that the Ser allele was more frequently observed in obese adolescents vs. the lean [44]. In that study, however, lower levels of sRAGE were linked to obesity [44].…”
Section: 0 Studies In Animal Modelsmentioning
confidence: 96%